Ecofriendly Synthesis of Silver Nanoparticles from Garden Rhubarb (Rheum rhabarbarum). (28th September 2016) - Reddy, Palem Ramasubba; Ganesh, Shimoga D.; Saha, Nabanita; Zandraa, Oyunchimeg; Sáha, Petr
Abstract : Bioreduction of silver ions following one pot process is described to achieve Rheum rhabarbarum (RR) based silver nanoparticles (SNPs) which is termed as "RR-SNPs." The Ultraviolet–visible spectroscopy (UV–vis) confirms the characteristic surface plasmon resonance band for RR-SNPs in the range of 420–460 nm. The crystalline nature of SNPs was confirmed by X-ray diffraction (XRD) peaks at 38.2°, 45.6°, 64.2°, and 76.8°. Transmission electron microscopy (TEM) and scanning electronic microscopy (SEM) confirm the shape of synthesized SNPs. They are roughly spherical but uniformly distributed, and size varies from 60 to 80 nm. These biogenic SNPs show persistent zeta potential value of 34.8 mV even after 120 days and exhibit potent antibacterial activity in presence of Escherichia coli (CCM 4517) and Staphylococcus aureus (CCM 4516). In addition, cytotoxicity of RR-SNPs against in vitro human epithelial carcinoma (HeLa) cell line showed a dose-response activity. The lethal concentration (LC50) value was found to be 28.5 μ g/mL for RR-SNPs in the presence of HeLa cells. These findings help us to evaluate their appropriate applications in the field of nanotechnology and nanomedicine.